Illegal insider trading: Commission and SEC detection - Cline, Brandon N.; Posylnaya, Valeriya V. (Journal of Corporate Finance, 2019)
Assessing illegal insider trading is challenging due to the nature of the activity. Researchers observe and evaluate only the detected portion of illegal trading, not all illegal transactions. This presents a problem when using traditional empirical techniques to investigate such activity. In our analysis we employ a bivariate probit model that takes into account the partial observability nature of insider trading and provides estimates for the determinants of both the commission and the detection of illegal insider trading. Among our findings, most notable is the deterrence effect of recent actions taken by the SEC to enforce insider trading laws. We highlight that insiders consider these actions when deciding to trade. We also illustrate the influence of the SEC's political structure on insider trading detection. We show that political party affiliation within the SEC, past indictments by the SEC, and SEC budget all play a crucial role in determining current prosecution.